Prevalence of clinical mastitis and its associated risk factors among dairy cattle in mainland China during 1982–2022: a systematic review and meta-analysis - Chen, Shuiyun; Zhang, Huiying; Zhai, Junjun; Wang, Honghai; Chen, Xuelong; Qi, Yanping (Frontiers in Veterinary Science, 2023)
Background: Bovine mastitis is one of the most common and expensive disease affecting the dairy cattle worldwide. It adversely affects the milk production as well as quality and leads to a significant production loss for the farmers. Methods: This article aimed to estimate the prevalence of CM infection in mainland China by using a systematic review and meta-analysis. The research reports published during 1983-2022 in English or Chinese from databases (PubMed, Google Scholar, Cochrane library, Clinical Trials, VIP, CNKI, and WanFang) were identified after reviewing the relevant scientific literature. Based on our inclusion criteria, this study analyzed the prevalence of CM in 47 published studies by meta-analysis. We extracted the total number of cattle infected with CM from the available studies, allowing us to estimate the prevalence of CM infection among the cattle in mainland China. Results: The pooled prevalence with the 95% CI for the clinical mastitis was (10% ,95%CI = 9,12). The prevalence of CM was associated with lactation, parity, age, with higher prevalence observed in late lactation (15%,95% CI=11,18) and mid-lactation (10%,95% CI=6,13) in comparison to early lactation (8% ,95% CI=5,10). The incidence of CM increased significantly with the increase of parity and age, and the highest incidence rates were(19%,95%CI=15,23) and (16%,95%CI=12,19) at parity and age ≥7, respectively. Among the seasons, the highest prevalence of CM infection was found in autumn (9% ,95% CI= 2,17). Interestingly, no significant effects were evident regarding the influence of quarter on the prevalence of CM.